The Making of Meat Satay by Using Bamboo Shoot Flour and Mackerel Flour (Rastrelliger sp.) Fortified with Bamboo Shoot Tempeh and Different Concentration of Stabilizers - Alex Septia Rusli; Herla Rusmarilin; Terip Karo-Karo (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The research was done to know the effect of arabic gum and xanthan gum and the effect of mackerel flour and bamboo shoot flour on the quality of the artificial meat satay by proximate analysis, water holding capacity, oil absorption, total microbial, tenderness, and organoleptics (colour, flavour, taste, and texture). The results showed that the ratio of mackerel flour and bamboo shoot flour had highly significant effect on moisture content, ash content, fat content, protein content, crude fiber content, water holding capacity, oil absorption, total microbial, tenderness, taste, and texture. The ratio of arabic gum and xanthan gum had highly significant effect on moisture content, ash content, protein content, water holding capacity, total microbial, and taste. The best quality artificial meat satay was a combination of 80% mackerel flour and 20% bamboo shoot flour and arabic gum of 0,5% and xanthan gum of 0,3% which based on taste and crude fiber content. Then, vitamin B12, calorie, and fatty acids were analysed. Therefore, artificial meat satay could be a source of health care food for the public. Keywords : arabic gum, artificial meat satay, bamboo shoot flour, , mackerel flour, xanthan gum